Perbedaan Kejadian Ikterus Neonatorum antara Bayi Prematur dan Bayi Cukup Bulan pada Bayi dengan Berat Lahir Rendah di RS PKU Muhammadiyah Surakarta - Saputra, Reza Gusni (2016)
Background: The infant mortality rate mainly caused by low birth weight infants (LBWI). LBWI is infants with birth weight less than 2500 grams. LBWI could happens to premature infants or term infants. LBWI infant, either the prematures and the term infants are the most occuring factors of the occurance of the icterus neonatorum. Icterus neonatorum or neonatal jaundice occured when bilirubin level on the blood raises that makes the skin and the sclera more jaundice. Objective: This study aimed to analyzed the difference of icterus neonatorum occurance between premature infants and term infants on low birth wieght at RS PKU Muhammadiyah Surakarta. Methods: This study use the observational analytic method with cross sectional approach, using simple random sampling, with 115 samples of low birth weight infants in 2015 at RS PKU Muhammadiyah Surakarta. The data gained from medical records at the medical records section, then the data analyzed with chi-square test. Results: Based on the result of chi-square test to know the difference of icterus neonatorum occurance between the premature infants and term infants with low birth weight infants, it shows a velue of p =0,000 (p<0,005). The icterus occurance on premature infants is 32,2% more than the term infants that gained 9,6%. Conclusions: There was a significant difference of the icterus neonatorum occurance between premature infants more than term infants on low birth weight infats at RS PKU Muhammadiyah Surakarta.